Comparative analysis of STP6 and STP10 unravels molecular selectivity in sugar transport proteins - Camilla Gottlieb Andersen; Laust Bavnhøj; Søren Brag; Anastasiia Bohush; Adriana Chrenková; Jan Heiner Driller; Bjørn Panyella Pedersen (Proceedings of the National Academy of Sciences, 2025)
The distribution of sugars is crucial for plant energy, signaling, and defense mechanisms. Sugar Transport Proteins (STPs) are Sugar Porters (SPs) that mediate proton-driven cellular uptake of glucose. Some STPs also transport fructose, while others remain highly selective for only glucose. What determines this selectivity, allowing STPs to distinguish between compounds with highly similar chemical composition, remains unknown. Here, we present the structure of Arabidopsis thaliana STP6 in an inward-occluded conformational state with glucose bound and demonstrate its role as both a glucose and fructose transporter. We perform a comparative analysis of STP6 with the glucose-selective STP10 using in vivo and in vitro systems, demonstrating how different experimental setups strongly influence kinetic transport properties. We analyze the properties of the monosaccharide binding site and show that the position of a single methyl group in the binding site is sufficient to shuffle glucose and fructose specificity, providing detailed insights into the fine-tuned dynamics of affinity-induced specificity for sugar uptake. Altogether, these findings enhance our understanding of sugar selectivity in STPs and more broadly SP proteins.